Analytic Study of Wife's Financial Rights Between Islamic law and Algerian Family Code law And between "Alkad Wa Alsi'ayah" Moroccan Code and The Indonesian Code of "Gono Gini" - Korichi, Elbadri, Dr.Muindinillah Basri, M.A (2013)
Research background states that Islam is the first to identify woman's rights and among them are financial rights. The problem is that other Islamic countries enact other financial laws to the wife caused by husband in case of divorce or dying. Based on this, the study confirmed wife's financial right from beginning of marriage till its end according to analytic, indicative study between Islamic Shari ah ك and Algerian family law from one side and between Moroccan hard work act and gono gini Indonesian law from the other. This research aims at collecting all sharia rules concerning wife's financial rules mentioned in Islamic jurisprudence books . Also objective analysis of Algerian family law, Moroccan hard work act, and gono gini Indonesian law. In the latter law we concluded following results: The Islamic Law (Shari ah) obligated the husband to give his wife her financial rights as she devoted herself for his service. Algerian family Code depend largely on Islamic law in issuing its rules. Alsi'ayah has its basis in Islamic law and it is general for everyone who contributed in developing finances. Gono gini Indonesian law isn't based on sound legitimate foundation and it concerns the wife only in developing money.